STRATEGI GURU PPKN DALAM MENINGKATKAN KEDISIPLINAN DAN KECERDASAN MORAL MELALUI PENERAPAN KODE ETIK SISWA KELAS X DI SMK PGRI 1 TULUNGAGUNG - Nanda Febriyanti, Erika; Agustina Rahayu, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the increasing violations of discipline among class X students at SMK PGRI 1 Tulungagung, which are influenced by various factors such as the post-pandemic impact, the development of digital technology, and changes in student characteristics. These conditions demand an effective strategy to develop students' discipline and moral intelligence, one of which is through the implementation of the student code of ethics. In this case, the Pancasila and Civic Education (PPKn) teacher has a strategic role because he/she shapes character through learning, habituation, role modeling, and moral guidance. The focus of this research is to determine the strategies of PPKn teachers in developing the discipline and moral intelligence of class X students through the implementation of the student code of ethics, as well as to identify the obstacles faced and the actions taken by teachers in implementing these strategies. This research uses a qualitative approach with a case study type. Data collection techniques include observation, interviews, and documentation, while data analysis follows the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. Data validity testing is conducted through source triangulation and technical triangulation. The results show that the strategies of PPKn teachers are carried out through five steps, namely teacher role modeling in behaving according to moral values, discipline habituation through the student code of ethics and school rules, providing continuous advice and guidance, integration of character values in PPKn learning, and the implementation of an educational reward and sanction system. The obstacles faced include low awareness among some students, the influence of the social environment, the uncontrolled use of social media, and suboptimal family support. As a follow-up, PPKn teachers provide intensive guidance, establish cooperation with parents and the school, take a personal approach to students, and carry out continuous evaluation and supervision. These strategies have proven effective in helping to improve students' discipline and moral intelligence through understanding and internalizing the values contained in the student code of ethics.